Quantifying the link: coronary artery inflammation via CCTA-derived fat attenuation index and its association with diabetes duration - Zhang, Yan; Wang, Jing; Song, Kexin; Yao, Zhuhua (Frontiers in Endocrinology, 2025)
AimsAlthough diabetes is a well-established enhancer of coronary inflammation, the specific relationship between diabetes duration and the degree of inflammation, as quantified by pericoronary fat attenuation index (FAI), remains poorly defined. This study aimed to investigate the association between diabetes duration and coronary inflammation, as assessed non-invasively by the pericoronary FAI derived from coronary computed tomography angiography (CCTA).Materials and methodsWe enrolled 468 adults with type 2 diabetes mellitus who underwent CCTA imaging. The pericoronary FAI was quantified around the three main coronary arteries. Multivariable linear regression and subgroup analyses were performed to evaluate the association between diabetes duration and pericoronary FAI. Potential non-linear associations were examined using restricted cubic spline (RCS) modelling.ResultsLonger diabetes duration was independently and positively associated with increased pericoronary FAI values in the LAD artery (β = 0.151, 95% CI: 0.064–0.238, P = 0.001), LCX artery (β = 0.101, 95% CI: 0.001–0.201, P = 0.047), and RCA (β = 0.208, 95% CI: 0.120–0.296, P < 0.001). RCS modelling revealed predominantly linear associations(P for non-linearity > 0.05). The association between diabetes duration and pericoronary FAI remained robust across the majority of examined subgroups.ConclusionProlonged diabetes duration is independently associated with elevated coronary inflammation, demonstrating a near-linear dose-response relationship.